VD_FINDINFO HC / 2014 / 679 vom 12. August 2014 - VD Tribunal cantonal (2014)
AVANCE DE FRAIS, CALCUL, DIVORCE SUR DEMANDE UNILATÉRALE | 103 CPC (CH), 319 let. b ch. 1 CPC (CH), 98 CPC (CH), 10 TFJC (2010), 54 TFJC (2010), 9 al. 1 TFJC (2010)